The Possibility of Generalizing Types of Basic Sentences in Bahasa Indonesia in Relation with the Learning of Basic Sentence Structure in English - Nana Suciati (International Conference on Education and Language (ICEL), 2014)
Learning English is not an easy task for our students.  It might because English itself is not practiced as second language, but more to target language.  Then it is only learned in certain situation like in school. That it is not easy is also probably because Bahasa Indonesia has different pattern of composing predicate. There are five types of basic sentences or simple sentences in Bahasa Indonesia based on their predicates in “Tata Bahasa Baku Bahasa Indonesia”.  The first type is sentence which is predicated by verb (ibumengajarbahasaInggris). The second type is predicated by adjective (ayahnyasakit). The third type is predicated by noun (dia guru saya). Further, the fourth one is predicated by number (rumahnyaduabuah). The last one is predicated by preposition (diakepasar).When making English sentences, it is common to find that students tends to translate purely from Bahasa Indonesia pattern.  Example, *his father sick, *his house two, and *I school.  These sentences are reflection of those former types of basic sentences in Bahasa Indonesia. It is what we call language interference and it is unavoidable. Instead of blocking this interference, it is better to find a similarity between two languagesEnglish has one type of predicate. This predicate is always verb, while in Bahasa Indonesia it can be in the form of noun, adjective, number, and preposition.  It is impossible to adjust English to Indonesian rules. However, it is probably possible to modify Indonesian rule to English rule for the sake of making students easier to learn English.  This paper proposes that all predicates in Bahasa Indonesia can be simplified into verb. Example, ayahnyasakit (ayahnyasedangsakit), dia guru saya (diaadalah guru saya), rumahnyaduabuah (rumahnyaberjumlahduabuah), diakepasar (diapergikepasar).By simplifying the five types of predicates in Bahasa Indonesia into one type of predicate, it is expected that interference from Bahasa Indonesia does not digress the English sentences made by students from the exact regulation.